The Role of Tax Incentives in Encouraging Innovation and Technology Adoption in Industrial Management - Suwanda, Suwanda (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
In the context of globalization and increasingly fierce industrial competition, technological innovation is the key to increasing the efficiency and competitiveness of an industry. This research will explore the relationship between tax incentives provided by the government and the level of innovation and adoption that occurs in industry, as well as its impact on industrial management. This research uses a qualitative approach with descriptive methods. The research results show that tax incentives play a crucial role in encouraging innovation and technology adoption in the industrial sector. Clear and flexible incentive designs have a positive impact, while factors such as complex provisions, policy uncertainty, and the availability of skilled labor can limit their effectiveness. Involvement in industrial collaboration, level of education, and positive perceptions of tax incentives also contribute to increasing the use of these incentives. In conclusion, the importance of designing tax policies that take into account the dynamics of the industry and business environment can create effective tax incentives in supporting innovative growth at the industry level.